Supply of rice (Oryza sativa) commodity in India: Insights on domestic production performance - SEKAR, I (The Indian Journal of Agricultural Sciences, 2014)
Food security is a critical issue in the developing world. India is the second largest producer of rice (Oryza sativa L.) next to China and rice accounts for larger proportion of human caloric intake in India. The price rise of rice commodity and conversion of rice lands for non agriculture purposes necessitate examining the existing status of rice production and suggesting measures to prevent any sort of disturbances in food security in India. This paper aims at analyzing the present production performance of rice in the country by examining the trends and shifts in production growth, delineating the sources of production growth as well as assessing the instability in rice production. In addition, some other critical issues of spatial differentials and price escalation are also discussed. The study reveals that there has been deceleration in growth rate of rice production and productivity not only in India but also in all the top five major rice producing countries in the world. There exists a spatial variation among Indian states, where northern and southern region registered higher rice productivity and the rest of the regions witnessed less productivity. Yield effect contributed more towards the decline in production growth in eastern states like West Bengal, Odisha and Asom and therefore it is required to have adequate measures to improve upon the yield growth. Besides, higher instability in rice production is also noticed in Odisha and Bihar. It is therefore important to have technology breakthrough in rice which could push the production trajectory path upwards and achieve a higher and sustainable growth rate in rice as well as sustaining food security status in India.